Existence of Reissner-Nordstrom type black holes in f(R) gravity - Mazharimousavi, S. Habib; Halilsoy, Mustafa; Kerachian, Morteza (International Journal of Modern Physics D, World Scientific Publishing, 2013)
We investigate the existence of Reissner-Nordstr\"om (RN) type black holes in f(R) gravity. Our emphasis is to derive, in the presence of electrostatic source, the necessary conditions which provide such static, spherically symmetric (SSS) black holes available in f(R) gravity. We also study the thermodynamics of the black hole solution
The file in this item is the post-print version of the article (author’s copy; author’s final manuscript, accepted for publication after peer-review process). Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1142/S0218271813500570)and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: general relativity; black holes; f(r) Gravity; Reissner–Nordstrom